2021
DOI: 10.3399/bjgpo.2021.0113
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of professional and patient-oriented strategies in reducing vitamin D and B12 test ordering in primary care: a cluster randomised intervention study

Abstract: BackgroundVitamin tests are increasingly ordered by GPs, but a clinical and evidence based indication is often lacking. Harnessing technology, ie, decision support tools and redesigning request forms, have been shown to reduce vitamin D requests.AimCould the number of vitamin tests also be reduced by providing a multi-level intervention programme based on training, monitoring and feedback?Design & SettingIn a Cluster Randomised Intervention Study performed in 26 primary care health-centres (200.000 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…A study among Dutch GPs showed that providing both education and feedback successfully reduced the amount of vitamin tests ordered by 20%–25%. 42 Similar interventions might therefore also be effective among hospital clinicians to reduce (non-indicated) vitamin testing. Alternatively, more emphasis could be placed on the institution of fortification and supplementation guidelines to achieve adequate vitamin B 12 and D intake among the Dutch population.…”
Section: Discussionmentioning
confidence: 99%
“…A study among Dutch GPs showed that providing both education and feedback successfully reduced the amount of vitamin tests ordered by 20%–25%. 42 Similar interventions might therefore also be effective among hospital clinicians to reduce (non-indicated) vitamin testing. Alternatively, more emphasis could be placed on the institution of fortification and supplementation guidelines to achieve adequate vitamin B 12 and D intake among the Dutch population.…”
Section: Discussionmentioning
confidence: 99%
“…All project teams performed a structured process evaluation, and all projects obtained ethical approval before the start of their study. Several projects are described in more detail in other papers 14–23…”
Section: Methodsmentioning
confidence: 99%